Effects of Factors Related to Shift Work on Depression and Anxiety in Nurses - Li, Yuxin; Wang, Yongchao; Lv, Xiaoyan; Li, Rong; Guan, Xiangyun; Li, Li; Li, Junli; Cao, Yingjuan (Frontiers in Public Health, 2022)
Abstract Background: Although shift work is the foundation of the provision of 24-hour continuous care in hospitals, it can negatively impact mental health in hospital workers such as nurses. Despite the connection between mental health and overall health, little is known about the effect of shift work-related factors on mental health in this population. Objectives: We investigated the effect of scheduling practices, physical and psychological characteristics related to shift work, and personal habits during shift work on depression and anxiety among nurses. Methods: In this multi-center cross-sectional study, 11,061 nurses from 20 hospitals in the Shandong Province of China completed an online survey between December 2020 and February 2022. Multivariate ordered logistic regression analysis was performed to examine shift-related factors associated with depression and anxiety in the study population. Results: The completion rate of all nurses' questionnaires was 83.00% (n = 9,181). Among the 9,181 respondents, 66.20% (n = 6,078) were shift nurses. Depression and anxiety were found in 58.82% and 62.08% of shift nurses, respectively, and these rates were influenced by fatigue during shift work, psychological stress before/during/after night shifts, feeling of being refreshed after resting before/after night shifts, using sleep medication before/after night shifts, physical discomfort during night shifts, busyness during night shifts, food intake during shift work, working > 40 hours/week during shift work, and sleep quality before/after night shifts. Conclusions: Depression and anxiety in shift nurses may be addressed by reducing their workload, sources of stress during night shifts, and facilitating rest and relaxation.